A Step Prior to REDD+ Implementation: A Socioeconomic Study - Anne Bernard; Nancy Gélinas (International Journal of Forestry Research)
Phase 2 of the United Nations’ REDD+ climate change mitigation initiative is underway in the Democratic Republic of Congo. Meanwhile, activities are being implemented to assess the reduction of emissions from deforestation and forest degradation. REDD+ projects need to include a social dimension; thus, the aim of this research was to understand how land-use relationships vary across communities in an area where a REDD+ project is planned. Specifically, we aimed to identify the primary income-generating activities, the variation in access to land, the potential for the development of community projects, and the implementation of alternative income-generating activities. In the summer of 2013, we assessed a REDD+ pilot project in and around the Luki Biosphere Reserve, Bas-Congo Province. We used participatory rural appraisal (PRA) methods in four communities located both inside and outside the reserve. We found that current subsistence income activities led to the destruction of forest habitat due to population pressure and a lack of alternative income-generating activities. Customary land tenures overlay statutory rights, which can often mean that community rights are threatened. To achieve their targets, REDD+ projects should consider the actual land-use patterns of local communities in order to generate sustainable income from the land.